2015
DOI: 10.1177/1363460714550909
|View full text |Cite
|
Sign up to set email alerts
|

‘Lad culture’ in higher education: Agency in the sexualization debates

Abstract: This article reports on research funded by the National Union of Students, which explored women students’ experiences of ‘lad culture’ through focus groups and interviews. We found that although laddism is only one of various potential masculinities, for our participants it dominated the social and sexual spheres of university life in problematic ways. However, their objections to laddish behaviours did not support contemporary models of ‘sexual panic’, even while oppugning the more simplistic celebrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 43 publications
1
59
0
1
Order By: Relevance
“…Even in the relatively anonymous online environment, a third of our sample reported that perpetrators were members of their online community. VAWG online and offline is often committed by lone men but harassment in public places, in particular, can have a public, performative aspect; Phipps and Young (2015) see 'laddish' harassment as a form of homosocial bonding. Online abuse is experienced in an ambivalent space that is simultaneously private and public.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the relatively anonymous online environment, a third of our sample reported that perpetrators were members of their online community. VAWG online and offline is often committed by lone men but harassment in public places, in particular, can have a public, performative aspect; Phipps and Young (2015) see 'laddish' harassment as a form of homosocial bonding. Online abuse is experienced in an ambivalent space that is simultaneously private and public.…”
Section: Discussionmentioning
confidence: 99%
“…Although feminist scholars have provided detailed, extensive and close-up critique of masculinity in crisis discourses, including in schooling contexts (Epstein et al 1998), the simultaneous mainstreaming of gender equity has arguably undermined feminism and weakened anti-sexist policies and practices in higher education (David 2016a). For example, although feminist research has exposed rape culture and 'lad culture' on campus (Phipps and Young 2015), feminist scholars argue that policies remain woefully inadequate, not only for students, but also for women and feminist academics (e.g. David 2016b; Burke, David, and Moreau 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the UK in recent years, there has been a growing focus on sexual consent between young people, largely emerging from concerns regarding unconsensual sexual encounters. Indeed there is a very real problem of high rates of sexual assault and, more broadly, a problem of 'lad culture' which has been highlighted as occurring within universities (Phipps andYoung 2015, Universities UK 2016) and within schools (Women and Equalities Committee 2016).…”
mentioning
confidence: 99%